2000
DOI: 10.1046/j.1471-4159.2000.0752427.x
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine 3‐Hydroxylase Inhibition in Rats

Abstract: Inhibition of kynurenine 3-hydroxylase suppresses quinolinic acid synthesis and, therefore, shunts all kynurenine metabolism toward kynurenic acid (KYNA) formation. This may be a pertinent antiexcitotoxic strategy because quinolinic acid is an agonist of NMDA receptors, whereas kynurenic acid antagonises all ionotropic glutamate receptors with preferential affinity for the NMDA receptor glycine site. We have examined whether the kynurenine 3-hydroxylase inhibitor Ro 61-8048 increases extracellular (KYNA) suffi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…When Ro61-8048 and other KMO inhibitors are administered to adult animals, their major effect is to increase the levels of kynurenic acid in the blood and tissues (Chiarugi et al ., 1995 ; Speciale et al ., 1996 ; Röver et al ., 1997 ; Cozzi et al ., 1999 ; Clark et al ., 2005 ), including at least 10-fold elevations in brain microdialysates in vivo (Urenjak & Obrenovitch, 2000 ) In the present study, Ro61-8048 was administered to pregnant rats at a dose that has been shown to increase kynurenic acid levels in the blood and brain of the pregnant dam and the brains of the embryos. An increase of 10–100-fold was produced after 5 h in utero ; the level returned to the control value in the mother after 24 h, but remained little changed in the embryos (Forrest et al ., 2013a ).…”
Section: Discussionmentioning
confidence: 76%
“…When Ro61-8048 and other KMO inhibitors are administered to adult animals, their major effect is to increase the levels of kynurenic acid in the blood and tissues (Chiarugi et al ., 1995 ; Speciale et al ., 1996 ; Röver et al ., 1997 ; Cozzi et al ., 1999 ; Clark et al ., 2005 ), including at least 10-fold elevations in brain microdialysates in vivo (Urenjak & Obrenovitch, 2000 ) In the present study, Ro61-8048 was administered to pregnant rats at a dose that has been shown to increase kynurenic acid levels in the blood and brain of the pregnant dam and the brains of the embryos. An increase of 10–100-fold was produced after 5 h in utero ; the level returned to the control value in the mother after 24 h, but remained little changed in the embryos (Forrest et al ., 2013a ).…”
Section: Discussionmentioning
confidence: 76%
“…Astrocytes represent one source of neuroprotective KYNA [ 6 , 20 ]; KYNA was presumed to have protective effect in neuronal cell death [ 21 , 22 ]. Studies have also suggested that an elevated extracellular KYNA level would be needed to act more effectively [ 23 ], leading to the idea of systemic administration of KYNA. This was not proved to be an ideal therapeutic option, as KYNA poorly penetrates the blood-brain barrier and it undergoes a rapid clearance from the brain and the circulation [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…KYNA was reported to act as an NMDA receptor antagonist (Ganong et al, 1983 ; Ganong and Cotman, 1986 ). However, although infusion with the KMO inhibitor Ro 61-8048 increased cerebral extracellular KYNA concentrations 10-fold, this did not lead to an inhibition of NMDA-mediated neuronal depolarization, a finding that challenges the notion that KYNA at near physiological levels directly modulates NMDA receptors (Urenjak and Obrenovitch, 2000 ). In contrast, increased KYNA in the brain induced by the KMO inhibitor JM6 decreased the extracellular cerebral L-glu concentration (Zwilling et al, 2011 ).…”
Section: Introductionmentioning
confidence: 92%